Optimization of Span 80-Croduret 50-Propylene Glycol as Emulsifier of Dried Strawberry Juice (Fragaria vesca L.) Emulgel and Permeation Test Through Shed Snakeskin Membrane - Ermawati, Dian Eka; Martodihardjo, Suwaldi; Sulaiman, TeukuNanda Saifullah (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Strawberry is a natural source of antioxidants with potential to inhibit melanin production in the skin. However, its application in topical formulations is limited by factors such as stability, skin permeability, and effective delivery, necessitating the development of an appropriate delivery system. This has led to the selection of double emulsion due to the water solubility of the active ingredient. To produce a stable emulsion, it is required to combine emulsifier with different hydrophilic-lipophilic balance values. This study aimed to obtain the optimal proportion of emulsifier combinations for formulating an emulgel containing dried strawberry. Antioxidant activity was evaluated using the DPPH assay, while the content of active compounds was quantified using the UV-Vis spectrophotometric method. The optimization of emulsifier proportions was carried out using the simplex lattice design (SLD), with globule size, viscosity, and separation ratio as response parameters. The optimized emulsion system was then incorporated into a hydrogel. Physicochemical stability of the emulgel was assessed based on organoleptic properties, pH, viscosity, spreadability, and phase separation. Permeation studies were conducted using Franz diffusion cells with shed snakeskin membrane as the diffusion barrier. The study successfully demonstrated that dried strawberry juice possesses antioxidant activity, with an IC₅₀ value of 0.331 mg/mL. The levels of key active compounds, namely quercetin (23.3% w/w) and anthocyanins (13.23% w/w), supporting its potential use in topical antioxidant applications. The most effective emulsifier system was determined to be a Span 80:Croduret 50:Propylene Glycol ratio of 1:2:1. This emulsifier composition yielded an emulsion with favorable droplet size, viscosity, and stability characteristics. Incorporation into a 1.5% Polygel CA hydrogel resulted in an emulgel formulation with excellent physicochemical stability, as indicated by consistent pH, spreadability, viscosity, and absence of phase separation during storage. Permeation studies using Franz diffusion cells showed that the optimized emulgel was capable of delivering 117.14 μg/cm² of flavonoids across shed snakeskin membrane within 5 hours, with a permeability coefficient of 2.84×10⁻⁵ μg/cm² and a flux rate of 6.6×10⁻⁵ μg/sec, indicating good skin permeation potential.